Analisis Kalimat Pragmatik Imperatif Pada Teks Prosedur Dalam Buku Bahasa Indonesia SMP Kelas VII Kurikulum Merdeka - Naazil Maharani An Nuur; Seffina Zenitha Jasmine; Santi Lufita Sari; Maissy Maula Fitriana; Fitria Hapsari; Amilia Buana Dewi Islamy; Asep Purwo Yudi Utomo (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
The research conducted this time focuses on analyzing imperative pragmatic sentences which include illocutionary acts in the procedure text contained in the Indonesian language book for junior high school grade VII of the Merdeka Curriculum. The purpose of this study is to analyze imperative sentences and find the types of imperative sentences used in procedure texts. The analysis technique used in this research is descriptive qualitative. This study uses two data collection techniques, namely listening and recording techniques. The listening technique applied is the free listening technique, because the analysis does not involve conversation. The data analysis method used in this research is using agih method and shown with formal and informal methods. Based on the results of the research conducted, it is found that the conclusion in the analysis of the procedure text shows the imperative sentences used in the text. In this research, imperative sentences are found that can be classified into various types. The author finds several types of imperative sentences, namely sentences that belong to the imperative of smooth, sentences that are part of the imperative of request, sentences that are imperative of request, imperative sentences of invitation, and sentences that are imperative of hope. The imperative meaning found in this study contains the intention to be able to command or request addressed to someone with the purpose of doing something.